(untitled) (Indonesian Minority Justice Review, 2025)
This paper explores the legal challenges faced by religious minorities in Indonesia, with a particular focus on the Ahmadiyya Muslim community. Despite Indonesia’s constitutional guarantee of religious freedom, the Ahmadiyya community has faced increasing persecution through a combination of legal restrictions, local government decrees, and societal discrimination. The study examines key legal frameworks, including the 1965 Blasphemy Law and the 2008 Joint Ministerial Decree on the Ahmadiyya, which explicitly prohibit the Ahmadiyya from practicing their faith publicly. By analyzing court rulings, government policies, and case studies of individual members of the Ahmadiyya community, the paper investigates how these legal instruments have been used to justify religious persecution. The paper also highlights the role of political forces in shaping laws that restrict religious freedom, particularly the increasing influence of conservative religious groups in Indonesian politics. Through interviews with legal experts, activists, and members of the Ahmadiyya community, the paper assesses the legal and social implications of these restrictions. The findings reveal that while legal protections for religious freedom exist on paper, in practice they are often undermined by political and social pressures that restrict the rights of religious minorities. The paper concludes by advocating for legal reforms that better protect religious freedom and address the root causes of religious discrimination in Indonesia.